Angel Gregorio : sometimes no plan leads to a better outcome - Thompson, Kenneth R., (SAGE Business cases., 2024)
Much of the common wisdom in business school relates to the importance of strategic planning and establishing performance metrics with carefully set processes and procedures to guide the development of a business. But sometimes, an open mind is a greater asset than the most intricate of plans. This is reflected in the entrepreneurial path of Angel Gregorio, founder of Spice Suite and Black & Forth in Washington, DC. Angel eschewed traditional planning and market research and spontaneously chose the business she would start during a brief discussion with the potential landlord where she was thinking of renting space. Within a few months she started Spice Suite, and a few months later she left her job as a school principal to devote herself full-time to a retail spice business in which she had no experience and no idea whether she would have a sustainable customer base.Who is this rule breaker? How did she create an exciting, profitable business and work at the same time to help other Black female entrepreneurs to achieve their dreams? Angel's excitement for life, for trying different paths, and for helping others makes her a role model for us all. While she did not have a written plan, there was one in her heart and in her values.